Innovation and smart destinations: Critical insights. (July 2020) - Williams, Allan M.; Rodriguez, Isabel; Makkonen, Teemu
Abstract: Smart destinations have become an esteemed concept among researchers and policy makers. Discussion of the concept is optimistic in tone and commonly linked to information rather than knowledge and more to design than innovation. This partly explains the relatively limited critical discussion of the (potential) benefits of smart destinations. The article raises selected issues from the innovation, as opposed to the design, literature to offer insightful perspectives on analyzing smart destinations. The discussion emphasises that: 1) smart destinations are driven by uncertainty; 2) knowledge provides deeper insights than information into smart destinations as innovation; 3) entrepreneurs play an important role in facilitating smart destinations; and 4) smart destinations constitute innovation systems. Highlights: Smart destinations are driven by uncertainty. Knowledge provides deeper insights than information into smart destinations. Entrepreneurs play an important role in facilitating smart destinations. Smart destinations constitute innovation systems. Innovation adds a more holistic perspective than design to understand smart destinations.